Assessment of nutrient amendments on stony coral tissue loss disease in Southeast Florida - Carreiro, Ashley M.; Eckert, Ryan J.; Sturm, Alexis B.; Ingalls, Thomas C.; Combs, Ian R.; Walker, Brian K.; Voss, Joshua D. (Frontiers in Marine Science, 2024)
Florida’s coral reefs are facing a multi-year outbreak of stony coral tissue loss disease (SCTLD) with dramatic consequences for coral communities. However, potential anthropogenic and environmental drivers of SCTLD progression and severity remain poorly understood. This study was designed to determine the potential impacts of nutrient amendments on the progression and spread of SCTLD on reefs in Southeast Florida. In situ fertilizer amendments with 30 g of Osmocote™ slow-release fertilizer were used to mimic the effects of agricultural and urban runoff. Fifteen healthy and thirty SCTLD-affected Montastraea cavernosa coral colonies were tagged and divided into three experimental groups: apparently healthy colonies, SCTLD-affected nutrient-amended colonies, and SCTLD-affected control colonies. SCTLD lesion progression, coral tissue loss, and disease prevalence were tracked over a 30-day nutrient amendment period and for an additional 40 days after nutrient amendment removal to determine if there were any latent or recovery effects. Coral tissue loss was tracked over time using Structure-from-Motion photogrammetry and disease prevalence was recorded from diver surveys within a 3-m radius surrounding five centroid colonies from each experimental group. Throughout the experiment, temperature, nutrient concentrations, and SCTLD status of the coral colonies were also monitored. Ultimately, we observed no significant differences in SCTLD progression or surrounding SCTLD prevalence between the nutrient-amended and control groups, suggesting that nutrient amendment had no effect on SCTLD severity during this experiment in Southeast Florida.